Derating active power filters considering network and bus voltage total harmonic distortions - Deilami, Sara; Masoum, Mohammad Sherkat; Moghbel, Moayed (2016)
The most practiced and acceptable approach to improve the power quality of distorted distribution networks is to install active power filters (APFs) at the point of common couplings (PCCs) of nonlinear loads. This approach has proven to be very effective since APFs fully compensate for the injected current harmonics at the PCCs that will effectively result in negligible voltage total harmonic distortion (THDv) of the entire network. The main drawback of APFs is that they are relatively expensive and not feasible for small facilities. This paper proposes a simple and practical approach for reducing the cost of APFs by derating them under the worst operating condition. The idea is instead of designing APFs to completely eliminate the injected current harmonics at their PCCs, reduce their ratings such that the overall network THDv is within permissible limit recommended by the power quality standards. Simulation results are presented and compared for the distorted IEEE 31 bus 23kV network without and with APFs considering different levels of filter deratings.